STRATEGY DEVELOPMENT FOR PURI ARTHA HOTEL USING COMPREHENSIVE STRATEGY-FORMULATION FRAMEWORK (A STUDY ON PURI ARTHA HOTEL IN YOGYAKARTA CITY) - RAMADHANA, PERMANA GEMILANG (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Strategy development for a company is the initial stage of the strategic management process, which consist of vision and mission development, identifying the company's external opportunities and threats, determining internal strengths and weaknesses, establishing long-term goals, formulating alternative strategies, and choosing specific strategies which will be implemented. This study uses the Comprehensive Strategy-Formulation Framework which consists of three stages; input stage, matching stage, and decision stage. The tools used in this study are the IFE Matrix, EFE Matrix, CPM, IE Matrix, SWOT Matrix, and QSPM. The samples were collected from Puri Artha Hotel?s employees, specifically the Head of Departments and Top Level Managers. The results of this is a developed strategy for Puri Artha Hotel to gain a competitive advantage against their competitors. The last strategy developed for Puri Artha Hotel is Market Penetration in order to strengthen Puri Artha?s position in the market, to keep up with its competitors. Maintaining strong relationships with OTA, giving special loyalty treatments for frequent and loyal guests, increase advertisements and held more events to promote Puri Artha?s brand, improving services and repairing broken or old facilities, and increase social media presence are the suggested actions.K?ywords: Strategy Development, Comprehensive Strategy-Formulation Framework, IFE, EFE, CPM, IE, SWOT, and QSPM